Ilmu-Ilmu Agama dalam Bingkai Al-Qur’an - Mohd Aji Isnaini (Wardah, 2016)
Abstract: Discourse holy book the al- Qur'an as a source of knowledge as well as handle the book of Muslims, has experienced its golden age, the period of the Daulah Umayyah and Daulah Abbasiyah. At this time the government is attempting to return golden period through UU No. 12 On Higher Education, which mentions the seven areas of arable PTAI, between the science of the main on faculty Ushuluddin, syariah adab, tarbiyah, philosophy, Islamic economy, which according to the authors are all framed in the holy book the al-Qur’an.